2020
DOI: 10.1038/s12276-020-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

Zeb1 for RCP-induced oral cancer cell invasion and its suppression by resveratrol

Abstract: Rab coupling protein (RCP) is upregulated in head and neck squamous cell carcinoma (HNSCC) and is correlated with the progression and survival of patients. However, the role of RCP in one of the aggressive types of HNSCC, oral squamous cell carcinoma (OSCC), remains elusive. In the present study, we identified the important role of Zeb1 in RCP-induced OSCC epithelial-to-mesenchymal transition (EMT) and invasion. RCP induces Zeb1 expression, and silencing Zeb1 expression significantly inhibits RCP-induced OSCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…RAB11FIP1 plays important roles in promoting cancer migration and invasion through regulating the expression of EMT-related proteins (Supplementary Fig. 8 A -C) [ 31 , 32 ]. Therefore, we hypothesized that circRTN4 stabilizes RAB11FIP1 in regulating EMT in PDAC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAB11FIP1 plays important roles in promoting cancer migration and invasion through regulating the expression of EMT-related proteins (Supplementary Fig. 8 A -C) [ 31 , 32 ]. Therefore, we hypothesized that circRTN4 stabilizes RAB11FIP1 in regulating EMT in PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that the upregulation of RAB11FIP1 and RAB11FIP2 and their interacting partner RAB11a promotes cancer migration and invasion [ 26 29 ]. RAB11FIP1 protects integrins from degradation, regulates cadherin recycling and promotes the expression of EMT-related transcription factors [ 27 , 29 , 31 , 32 , 61 , 62 ]. In this study, we found that circRTN4 promotes EMT via RAB11FIP1-mediated upregulation of N-cadherin, Slug, Snai1, Twist and Zeb1 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that the cooperation of integrin b1 and EGFR is dependent on Rab11-FIP1 (13,16,20,21). In some cells, this was dependent on stimulation with the EGFR ligand EGF, or with the avb3 integrin ligand osteopontin (13).…”
Section: Mutant P53 and The Role Of Rab11-fip1 In Integrin/rtk Signallingmentioning
confidence: 87%
“…A recent study reported that Rab coupling protein (RCP) induces OSCC invasion and EMT by expressing Zeb1 and MT1-MMP. Resveratrol was reported to inhibit RCP-induced OSCC invasion by downregulating Zeb1 and β1 integrin expression [ 78 ].…”
Section: Phytoextracts/phytoconstituents For the Treatment Of Oral Cancermentioning
confidence: 99%